ASUHAN KEPERAWATAN PENATALAKSANAAN PENURUNAN CURAH JANTUNG PADA TN.T DENGAN CONGESTIVE HEART FAILURE (CHF) DENGAN SLOW DEEP BREATHING DI RSUD.PROF.DR.MARGONO SOEKARJO PURWOKERTO - Amanda Aditya Susanti,; Ikit Netra W, (Jurnal Cakrawala Ilmiah, 2023)
Heart failure is a condition of the heart's inability to pump enough blood to meet the tissue's need for oxygen and nutrients due to abnormalities in heart function which results in the heart failing to pump blood to meet the metabolic needs of the tissue. Slow deep breathing is an act that is done consciously to regulate breathing slowly and deeply so as to cause a relaxing effect. Purpose: This case study discusses the implementation of slow deep breathing in heart failure patients with a nursing diagnosis of decreased cardiac output. Method : Case study was conducted on 1 patient by applying Slow deep breathing for 3 days from 12 to 15 December 2022. Results : After being given nursing actions for 3 days, the nursing diagnosis of decreased cardiac output related to afterload changes is resolved marked by saying chest pain rarely occurs , breath is not shortness. Conclusion: Slow deep breathing affects the problem of decreased cardiac output.